3D Mosaic Carbon Nanofiber Sensors for Room‐Temperature Detection of Methane and Other Dissolved Gases in Transformer Oil. Issue 7 (19th January 2023) - Xu, Chengcheng; Yang, Jingjing; Wang, Yang; Zheng, Xing; Long, Yin; Du, Hongfei; Li, Xian; Bai, Chunjiang; Du, Xiaosong
Abstract: Hydrocarbons and carbon oxides are typical dissolved gases in transformer oil that reflect the latent pitfalls, on‐line monitoring of their concentrations can effectively evaluate the operating status of the power transformer. However, these low‐concentration targets (especially for CH4 ) show high chemical inertness at room temperature, challenging the sensitive performance of current commonly used chemiresistive gas sensors. Herein, a strategy by combining traditional inorganic semiconductors to carbon nanofiber (CNF) via electrospinning–annealing route is described. Three optimized 3D mosaic films, CNFs scaffold incorporated with WO3, SnO2 and MoS2 nanoparticles, are obtained. Due to the large specific surface area of the 3D network, and the synergic and heterojunction effects between nanoparticles and CNFs, all three sensors exhibit high response to CH4 at room temperature, and also record distinguishable signals toward H2, C2 H4, CO and CO2, revealing the three sensors are cross‐sensitive to the five analytes. Accordingly, preliminary discrimination of five dissolved gases is realized by principle component analysis. This study provides an effective and extendable solution of preparing room‐temperature chemiresistive sensors for the detection of CH4 and other gases, and offers a strategy for the construction of sensor array to achieve a high discrimination capability. Abstract : Three mosaic sensors, that is, WO3 /carbon nanofibers (CNFs), SnO2 /CNFs and MoS2 /CNFs, are prepared through an efficient electrospinning and the followed thermal treatment strategy, showing high room‐temperature sensibility, low detection concentration and cross‐sensitivity to methane and other four target analytes in transformer oil, and preliminary discrimination of these target analytes is realized by principle component analysis.